A new type of bentonite-based non-woven composite - Rosić Branko; Jovanović Dušan; Lukić Slavenka; Jović-Jovičić Nataša; Banković Predrag; Dostanić Jasmina; Milutinović-Nikolić Aleksandra (Journal of the Serbian Chemical Society, 2011)
Sandwich-like composites based on clays and textiles are extensively applied in various fields, including civil engineering and environmental protection. In this paper, the synthesis of a new type of composite with embedded bentonite particles within a non-woven polyester matrix is presented. The synthesized composite has improved mechanical properties compared to the corresponding non-woven matrix. Although more than two-times thinner, the synthesized composite showed mechanical properties similar to those of a commercial composite chosen for comparison. Sorption test results confirmed that the contribution of the textile component to the sorption of aqueous Cu(II) ions by the composite was negligible. The sorption of aqueous Cu(II) ions on the synthesized composite was best-fitted using the Langmuir model. The presented study confirmed that the loss of bentonite particles from the composite can be eliminated using the suggested synthesis method.